The impact of COVID-19 on neurosurgical head trauma referrals and admission at a tertiary neurosurgical centre. (May 2021) - Sinha, Siddharth; Toe, Ko Ko Zayar; Wood, Edith; George, K. Joshi
Highlights: COVID-19 has greatly impacted surgical specialities throughout the globe. Neurosurgical Admissions and length of stay greatly reduced during lockdown. The impact of COVID-19 on neurosurgery can help we plan for future pandemics. Considerations need to be taken for trainees to sufficiently complete training. Abstract: Background: COVID-19 has greatly impacted surgical specialities throughout the globe leading to a decrease in hospital admissions and referrals. Neurosurgery has seen a great decline in cases including head trauma leading to a negative impact on the development of neurosurgical trainees. The main objective of this study is to the identify changes in neurosurgical referrals, admissions and management during the COVID-19 pandemic. We also aim to assess how current practise could be adapted to help manage future pandemic peaks. Methods: Data was collected for the first 31 days of lockdown during 2020 (23rd March – 22nd April) and compared to the same time period in the years 2016–2019. We assessed the number of referrals, admissions and clinical information of patients during this period with a key emphasis on head trauma. Results: Neurosurgical head injury referrals and admissions reduced by 57.5% and 48.3% respectively during the first 31 days of lockdown when compared to the mean figures for the same period in the previous 4 years. This was also seen with head trauma with a 21.9% decline in referrals and 39.1% reduction in admissions for the period of interest. A significant decrease in length of stay (P < 0.001) was seen between 2020 and the years 2017–19. Conclusion: The impact of COVID-19 makes it imperative that we plan for future pandemics to lessen the impact on neurosurgery. Special considerations need to be taken so that trainees are sufficiently prepared for completion of training whilst still priotising patient safety and providing high quality care.